ANALISIS KESEHATAN DAN KESELAMATAN KERJA PADA LABORATORIUM DENGAN MENGGUNAKAN JSA - Husna , Nabila (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The inumber iof iaccident icases iin iIndonesia iis iincreasing ifrom iyear ito iyear, iand ithe ilatest idata iin i2018 iwas i157,313 iwork-related iaccidents. iThe ilaboratory iis iinseparable ifrom ithe ipotential idangers iand irisks iof iwork-related iinjuries ifrom ipractical itools iand imaterials ifor ipractitioners. iWork ito iprevent iand icause iwork iaccidents iin ithe ilaboratory iby iimplementing iJob iSafety iAnalysis i(JSA) iand iincreasing iknowledge iabout ioccupational isafety iand ihealth i(K3). ilearn iabout ithe iapplication iof iJSA, iK3 iabout ithe irate iof iwork iaccidents iin iuniversity ilaboratories. iThis itype iof iresearch iis ia iquantitative ianalysis iobservation imethod iwith ia icross isectional idesign, iand ithe isample iin ithis istudy iwas i155 irespondents iwith iinclusion iand iexclusion icriteria. iThe ip ivalue iof ithe istatistical itest iresults iof ithe iapplication iof iJSA iand ithe iincidence iof iindustrial iaccidents iis i0.000. iThis ishows ithat ithere iisisignificant irelationship ibetween ithe iapplication iof iJSA iand ithe iincidence iof iwork iaccidents. Therefore the iapplication iof iJSA iis ian ieffort ito iprevent iand iminimize ithe iincidence iof iwork iaccidents ifor ipractitioners iand iknowledge iof iK3 ias ia ibasis ifor iunderstanding iand ipracticing iwork iin ithe ilaboratory.